Catalytic systems for the H2S wet oxidation at room temperature - Lee, Eun-Ku; Jung, Kwang-Deog; Shul, Yong-Gun (SPRINGER/PLENUM PUBLISHERS, 2007)
The catalytic wet oxidation process is the most attractive process for small-scale hydrogen sulfide (H2S) removal from natural gas. The catalytic wet oxidation process is anticipated to be cost effective and simple so that it can be used for treating sour gases containing small amounts of H2S and can be easily operated even in isolated sites. The development of effective catalyst is the key technology in the wet catalytic oxidation of H2S. The scale of operation for the process has to be flexible so its use will not be limited by the flow rates of the gas to be treated. The heterogeneous catalytic wet oxidation of H2S has been attempted on activated carbons, but the H2S removal capacity still shows the low removal efficiency. The catalytic wet oxidation of H2S was studied over Fe/MgO for an effective removal of H2S. In order to develop a sulfur removal technology, one has to know what surface species of catalyst are the most active. This article discusses the following systematic studies: (i) the catalytic preparation to disperse Fe metal well on MgO support for enhancing H2S removal capacity, (ii) the effect of the catalytic morphology on the activity of Fe/MgO for the H2S wet oxidation, (iii) the influence of precursor and support on the activity of Fe/MgO for catalytic wet oxidation of H2S to sulfur.
Keywords: SELECTIVE OXIDATION; ELEMENTAL SULFUR; IRON-OXIDE; FE/MGO CATALYSTS; HYDROGEN-SULFIDE; PRECURSORS; XPS